Expression and Purification of PhoR Sensor-Domain Histidine Kinase of Mycobacterium tuberculosis in Escherichia coli - ERNAWATI ARIFIN GIRI-RACHMAN; FENRYCO PRATAMA; OKTIRA ROKA AJI; ARUM PATRIATI; IHSANAWATI IHSANAWATI; MAELITA RAMDANI MOEIS; EDY GIRI-RACHMAN PUTRA (Microbiology Indonesia, 2015)
Globally, tuberculosis (TB) remains a leading cause of death. The emergence of multidrug-resistant strains (MDR-TB) and extensively drug-resistant strains (XDR-TB) has fuelled the discovery for novel drugs and drug targets for its successful and better treatment. One of the potential candidates for drug target is PhoR sensory protein histidine kinase, a part of the Two Component System (TCS) PhoP/PhoR in Mycobacterium tuberculosis (Mtb). This protein system was known for its role on regulating hundred of Mtb virulence factors, from genes for cell wall and lypid synthesis to genes for adaptation in human leukocyte and hypoxia response. Previous studies have successfully characterized, isolated, and cloned the putative sensory domain of PhoR protein gene into pRSET vector expression system. In this study, Escherichia coli was transformed with pRSET-SensPhoR and cultivated at 37oC under IPTG induction to express PhoR sensor-domain protein. Most of the proteins were overexpressed in the form of inclusion bodies.  Subsequent protein purification in Ni-NTA system under refolding condition on urea gradient was performed to isolate PhoR sensor-domain protein in soluble form. Arginine was supplemented in purified protein solution to prevent aggregation during long term storage.  While highly purified protein was acquired, small angle X-ray scattering (SAXS) analysis was conducted to obtain 3-dimensional (3D) protein structures in solution.    doi:10.5454/mi.9.2.1